Production of Hydroxycarboxylic Acid Receptor 3 (HCA3) Ligands by Bifidobacterium - Takuma Sakurai (MDPI AG, 2021)
Hydroxycarboxylic acid receptor 3 (HCA3) was recently identified in the genomes of humans and other hominids but not in other mammals. We examined the production of HCA3 ligands by Bifidobacterium spp. In addition to 4-hydroxyphenyllactic acid, phenyllactic acid (PLA), and indole-3-lactic acid (ILA), we found that LeuA was produced by Bifidobacterium as an HCA3 ligand. The four ligands produced were the mixtures of enantiomers, and D-ILA, D-PLA, and D-LeuA showed stronger activity of the HCA3 ligand than their respective L-isomers. However, there was no difference in AhR activity between the two ILA enantiomers. These results provide new insights into the HCA3 ligands produced by Bifidobacterium and suggest the importance of investigating the absolute stereo structures of these metabolites.